Strategi Kebijakan Pemulihan Ekonomi Berdasarkan Perspektif Critical Realism Pada Disruption Di Indonesia - Allen Pranata Putra; Agung Bayu Murti (Journal of Trends Economics and Accounting Research, 2023)
Researchers observe that after the second wave of Covid-19 is an economic revival, countries that recover faster from the economic crisis are countries that are ready to win market competition. The urgency of this research is that the acceleration of economic recovery in Indonesia is very important to observe and analyze. The formulation of this research problem has two things, namely: 1) What is the potential for economic recovery based on the perspective of critical realism in disruption in Indonesia? 2) How is the optimization of economic recovery policy strategy in Indonesia? The stages of research methods to achieve research objectives are qualitative through the use of in-depth interviews, focus group discussions and observations. The results show that the priority program of import substitution policy has been implemented to reach 35% in 2022 and is predicted to continue to be increased as an effort to improve the national trade balance. The priority program for import substitution policy has been implemented to reach 35% in 2022 and is predicted to continue to be increased as an effort to improve the national trade balance.